Mechanisms of Inflammation in Proliferative Vitreoretinopathy: From Bench to Bedside - Stavros N. Moysidis; Aristomenis Thanos; Demetrios G. Vavvas (Mediators of Inflammation)
Proliferative vitreoretinopathy (PVR) is a vision-threatening disease and a common complication of surgery to correct rhegmatogenous retinal detachment (RRD). Several models of the pathogenesis of this disease have been described with some of these models focusing on the role of inflammatory cells and other models focusing on the role of growth factors and cytokines in the vitreous which come into contact with intraretinal and retinal pigment epithelial cells. New experiments have shed light on the pathogenesis of PVR and offer promising avenues for clinical intervention before PVR develops. One such target is the indirect pathway of activation of platelet-derived growth factor receptor alpha (PDGRα), which plays an important role in PVR. Clinical trials assessing the efficacy of 5-fluorouracil (5-FU) and low-molecular-weight heparin (LMWH), daunorubicin, and 13-cis-retinoic acid, among other therapies, have yielded mixed results. Here we review inflammatory and other mechanisms involved in the pathogenesis of PVR, we highlight important clinical trials, and we discuss how findings at the bench have the potential to be translated to the bedside.